Updated distribution of spotted hyaenas in Gabon reveals resident populations - (:unkn) unknown (My University, 2024)
Spotted hyaena distribution currently widely encompasses sub-Saharan Africa, apart from the Congo Basin. Formerly described as residents of Gabon but considered extinct, vagrant individuals have been recorded since 2003, but no systematic species presence assessment has been made. Based on records of killed individuals, tracks and camera-trap sightings, we show that not only vagrant individuals are roaming in Gabon, but a small resident population occurs in the North-East of the country. The records collated here formed the basis for spotted hyaenas to be listed as protected in Gabon, were included in the IUCN Red List species' range map update and showcased the importance of large-scale by-catch data analysis in updating species distributions.
Keywords: African Research